MEMAKNAI FITRAH MANUSIA: Satu Pola Interaksi Hadis Dengan Al-Qur’an - Sri Naharin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2015)
Fitrah is a popular term which is often related to the sanctity of human life. Fitrah is synonymous with the holy and pure. Especially at the end of the month of Ramadan, it becomes interesting term because there are two sentences namely 'Idul Fitri' and 'zakat fitrah' which means a symbol of someone who has returned to fitrah: human nature. Even the term of fitrah is categorized in such good concept in both religion, science or education. This paper attempts to unravel and exmine the nature of fitrah in the perspective of the two sources where which the term is derived, namely Hadith and Quran, especially the fitrah in the context of human nature. Hadith and the Qur'an explains the meaning of ‘fitrah’ by 'Islam'. In this context Islam is not understood as a religion or an institution but rather to provide an understanding that 'Islam' is an act of submission to the Creator. Every human being is born as an 'Islamic' and have their potential faith. However, if a person comes to leave such fitrah with the passage of time, it is due to the external factors. The only way that can make human being to ‘the fitrah’ is “Islam” as the original religion of fitrah through the teachings of the 'kitab al-‘alam’ and the Quran.